Valor presente para IFRS no Brasil: um estudo das taxas apropriadas para calcular o valor justo de instrumentos financeiros de renda fixa - Securato, Sergio (2014)
The migration of Brazilian financial statements to international standards has been a major challenge due to cultural change of the two models. It is the migration of a model that has always suffered strong regulatory influence and is based on defined rules for a model based on principles, judgment and economic substance of transactions. In Brazil the CPC is the committee responsible for directing the Brazilian accounting standards to international standards set by the IASB through IFRS. Given the recommendations of the technical pronouncement CPC 12, which deals with the adjustment to present value, we seek to address in this thesis the concept of fair value and market value, understanding that we can define a hierarchy for fair value calculus, where we prioritize observable market values. When we don t have an available market, it is recommended to use a model for the definition of the risk premium that can generate information, to the extent possible, to replicate the market behavior. In this way, this study assessed based on the risk premium initially defined, the use of a model that can provide this award during the life of the transaction, thus allowing the creation of a interest rate structure that will help in assessing the fair value of financial fixed income assets and liabilities when there is no active market